Monolithic Perovskite/Perovskite/Silicon Triple-Junction Solar Cells: Fundamentals, Progress, and Prospects - Leiping Duan; Xin Cui; Cheng Xu; Zhong Chen; Jianghui Zheng (Nano-Micro Letters)
Highlights Perovskite/perovskite/silicon triple-junction solar cells (PSTJSCs) are emerging as a promising strategy to exceed the efficiency limits of traditional silicon solar cells. This review systematically analyses the key principles, recent breakthroughs, and remaining challenges in PSTJSC development, including current mismatch, open-circuit voltage loss, phase segregation, and stability. Strategies to address these issues and future directions toward achieving high efficiency and long-term operational stability are comprehensively discussed.